APLIKASI TEKNOLOGI EKSPLORASI UNTUK MENGKAJI SUMBERDAYA AIR TANAH DAERAH TELAGA BANTA, KABUPATEN TANAH DATAR - Prayogo, Teguh (Jurnal Hidrosfir Indonesia, 2009)
Water is a component in the earth that is very important for human life. Theavailability of water is always wanted to meet a demand of water supply,such as for drinking water, washing, taking a bath, and etc. Along withpopulation growth, so the need of water will be still increasing, includingTanah Datar. In this paper will be described concerning to characteristics,and condition of water in Tanah Datar Area, West Sumatera Province,especially Telaga Banta. This location occupies geographically between thelatitude of 00o17’ and 00o39’ south and the longitude of 100o19’ and 100o51’east Based on survey in field, condition of aquifer in Telaga Banta is locatedin 20 – 60 meter depth, and the result of laboratory points to that the qualityof water in this area meets the requirement for drinking water.